Kemudahan Pencatatan, Monitoring, dan Pelaporan Kesehatan Lansia dengan Pemanfaatan Sistem Informasi Kesehatan Lanjut Usia Silanu Amombo - Usman, Reni Devianti; Rahayu, Dian Yuniar Syanti; Paluala, Dwi Purnama Putri (Health Information : Jurnal Penelitian, 2022)
Utilization of information systems and technology to provide convenience, efficiency, and effectiveness of health service administration in the primary sphere. This research is an experimental question study on primary service facility (posyandu) cadres which were carried out from July to December 2020 in the working areas of Puskesmas Soropia and Puskesmas Lalonggasumeeto, Konawe Regency, Southeast Sulawesi. There were 28 cadres and 2 elderly data programmers at Puskesmas Soropia, 2 cadres and 1 elderly data programmer at the Puskesmas Lalonggasumeeto, so that a total of 33 respondents. The method of collecting data from the use of the Silanu Amombo application by elderly cadres and programmers uses a feasibility questionnaire for using the application which is given to respondents after the collection of elderly health data is complete. The results showed that Silanu Amombo was easy to use (100%) the symbols on the application were clear (96.97%), the images on the application were clear (100%), the Silanu Amombo application was useful for the health of the elderly (100%), and for data collection on the elderly ( 100%). The Silanu Amombo elderly health information system helps the process of recording, monitoring and reporting the health of the elderly.